Accounting Geared towards Corporate Social Responsibility: Analysis of the Polish Insurance Sector - Obora, Patryk (Rachunkowość ukierunkowana na społeczną odpowiedzialność biznesu: analiza polskiego sektora ubezpieczeń, 2022)
The aim of the study was to present the way in which non-financial information associated with Corporate Social Responsibility (CSR) is reported in the Polish insurance sector. Moreover was intended to check the engagement of Polish insurance companies in non-financial reporting and to determine in which areas they are socially responsible. Non-financial reporting is facing many problems which derive from the lack of uniform standards and regulations. The research was carried out by compiling the existing data on the official websites of insurance companies and elaborating a case study of Ergo Hestia. A role model of transparent CSR reporting is the social report of the Ergo Hestia Group from 2020, which was prepared in accordance with GRI (Global Reporting Initiative) standards, the UN “2030 Agenda for Sustainable Development” goals and the principles of “Good Practice”. The study shows that the insurance market is insufficiently involved in sustainable development issues and focuses primarily on building a good reputation. The social commitment of companies outweighs other areas of CSR, which makes the comparison process difficult to realise.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 2, s. 34-48
Keywords: corporate social responsibility; Global Reporting Initiative; non-financial reporting standards; insurence companies; społeczna odpowiedzialność biznesu; ESG; niefinansowe standardy sprawozdawczości; zakłady ubezpieczeń